The association of family structure with health behavior, mental health, and perceived academic achievement among adolescents: a 2018 Korean nationally representative survey - Hanul Park; Kang-Sook Lee (BMC Public Health, 2020)
Abstract Background Adolescence is a period during which physical, social, and mental abilities are rapidly developed, and during this time the family environment plays an important role. Differences in health behaviors, mental health, and academic achievement by family structure may affect future families, income, and employment. The purpose of the study was to investigate the association of family structure with health behaviors, mental health, and academic achievement in Korean adolescents. Method Data from the 2018 Korean Youth Risk Behavior Web-based Survey were analyzed. The study sample was comprised of 59,096 adolescents. Logistic regression, t-tests, and a variance analysis of a complex sample general linear model were used to examine the association of family structure with health behaviors, mental health, and academic achievement. The significance level was set at P < 0.05. Results Non-intact families (single-mother families, single-father families, and restructured families) had significantly higher odds of smoking a cigarette, drinking a sip of alcohol, internet use, physical activity, and sexual experience, and mental health issues such as depression, suicidal ideation, perceived stress, and poor perceived health status than intact families (two-parent families). Also, non-intact families were significantly related to low perceived academic achievement compared to intact ones. Conclusion This study showed that family structure is a significant factor in adolescent health behavior, mental health, and perceived academic achievement. Adolescents who experience a transition in their family structure may be more vulnerable to health risks and exhibit lower academic achievement than those in an intact family.